Experience Of Living With Islam-Christianity In North Maluku, Indonesia - Botara, Sirayandris J. (International Journal of Educational Research & Social Sciences, 2022)
The article starts from the experience of living with Islam-Christians in the North Maluku province of Indonesia infacing the threat of the spread of the Corona Virus Disease (COVID-19) pandemic. This religious community, whichhad a conflict in 1999, has a different way of dealing with the spread of COVID-19 with other regions in Indonesia,both regarding the views of positive Covid-19 patients who care for sin and reward, Islamophobia, and physicalworship. continues in buildings of worship during the pandemic. These incidents occurred in the North Malukuprovince of Indonesia as a border area with a distinctive social, cultural and political context, so the field tracingused was a case study. This is in line with the empirical reality of the spread of COVID-19 which is still ongoing, soresearch was conducted intensively participatory in the Muslim-Christian community in North Maluku province. Inthe process of investigating data, informatory are needed, but the question of how the Muslim-Christian communityin North Maluku continues to care for life together amid the COVID-19 pandemic is the main question of thisresearch. Of course, many research articles on COVID-19 have been published, but there has not been a singlestudy on Islamic-Christian relations during the pandemic, let alone a case study of the Muslim-Christiancommunity, which once fought to the point of casualties and is now facing non-natural disasters. The answers to themain research questions will be a contribution of thought for anyone who has the desire to care for their communitythat supports each other. So that a case study of the Muslim-Christian community who has been in conflict andinhabits the coast of eastern Indonesia and is now facing the threat of COVID-19 is an important agenda andcloseness. The value premise of this study is to learn the pattern of relations in the community after the riot betweenMuslims and Christians and religious communities, this non-natural disaster along the spread of COVID-19. As faras the author's knowledge, this study is the latest study on the Muslim-Christian community in North Maluku in theface of COVID-19. These two communities are able to get through difficult times of horizontal conflict, this studywill study how the two religious communities can face the challenges of COVID-19 and become a strong generationafter all of this has passed.